Impact of cumulative operative time on postoperative complication risk in simultaneous resections of colorectal liver metastases and primary tumors. Issue 3 (March 2023) - Martin, Allison N.; Tzeng, Ching-Wei D.; Arvide, Elsa M.; Skibber, John M.; Chang, George J.; Nancy You, Yi-Qian; Bednarski, Brian K.; Uppal, Abhineet; Dewhurst, Whitney L.; Cristo, Jenilette V.; Chun, Yun S.; Tran Cao, Hop S.; et al.
Abstract: Background: Simultaneous resection of colorectal liver metastases (CLM) and primary colorectal cancers (CRC) is nuanced without firm rules for selection. This study aimed to identify factors associated with morbidity after simultaneous resection. Methods: Using a prospective database, patients undergoing simultaneous CLM-CRC resection from 1/1/2017-7/1/2020 were analyzed. Regression modeling estimated impact of colorectal resection type, Kawaguchi–Gayet (KG) hepatectomy complexity, and perioperative factors on 90-day complications. Results: Overall, 120 patients underwent simultaneous CLM-CRC resection. Grade≥2 complications occurred in 38.3% (n = 46); these patients experienced longer length of stay (median LOS 7.5 vs. 4, p < 0.001) and increased readmission (39% vs. 1.4%, p < 0.001) compared to patients with zero or Grade 1 complications. Median OR time was 298 min. Patients within highest operative time quartile (>506 min) had higher grade≥2 complications (57%vs. 23%, p = 0.04) and greater than 4-fold increased odds of grade≥2 morbidity (OR 4.3, 95% CI (Confidence Interval) 1.41–13.1, p = 0.01). After adjusting for Pringle time, KG complexity and colorectal resection type, increasing operative time was associated with grade≥2 complications, especially for resections in highest quartile of operative time (OR 7.28, 95% CI 1.73–30.6, p = 0.007). Conclusion: In patients undergoing simultaneous CLM-CRC resection, prolonged operative time is independently associated with grade≥2 complications. Awareness of cumulative operative time may inform intraoperative decision-making by surgical teams.